2013
DOI: 10.1002/ajmg.a.35903
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Networking Sites in Medical Genetics Research

Abstract: Social networking sites (SNS) have potential value in the field of medical genetics as a means of research subject recruitment and source of data. This article examines the current role of SNS in medical genetics research and potential applications for these sites in future studies. Facebook is the primary SNS considered, given the prevalence of its use in the United States and role in a small but growing number of studies. To date, utilization of SNS in medical genetics research has been primarily limited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…As proposed by Hefler et al, social media strategies may be integrated into tobacco control organizations [5]. Moreover, social media, such as Facebook, already include information about many disorders and genetic syndromes [6]. …”
Section: Introductionmentioning
confidence: 99%
“…As proposed by Hefler et al, social media strategies may be integrated into tobacco control organizations [5]. Moreover, social media, such as Facebook, already include information about many disorders and genetic syndromes [6]. …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] The anonymity guaranteed by online surveys are of benefit if study topics are personal or taboo, such as questions on sexuality as in the case of HPV, where household or schoolbased recruitment strategies may be less favorable. 16,17 Recently, a study used Facebook to collect data on knowledge of HPV and cervical cancer among young women in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Samples recruited from social media networks tend to have an overrepresentation of females and younger adults. 15 One study, which compared traditional with online advertisement recruitment found that men, young adults, ethnic minorities, and a high school education or less were more likely to be recruited via online advertizing. 19 In the current study, we were able to adjust the targeting strategy based on an interim analysis of key characteristics, thereby optimizing the study sample composition; the focused targeting strategy applied during the second phase was successful in increasing the proportion of lower educated women and women with a migrant background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…due to an increase in exclusive use of mobile phones or email rather than traditional mail or landline phone. Opportunistic approaches such as recruitment via social media promise cost savings [4,[7][8][9][10][11][12] and a better coverage of person groups that are hard to reach with the traditional recruitment methods, like parents of adolescents [8], adolescents themselves [10], people with special conditions [13,14], smokers [15] or low-income people [16]. Social media, like Facebook and Twitter, can potentially have a strong snowballing effect [17] given their intensive use and continuing growth (around 1.94 billion monthly active Facebook users worldwide [26]), their feature that information can be shared very easily among networks [17], and are therefore able to reach a large number of people in a very short time.…”
Section: Introductionmentioning
confidence: 99%